Severe acute heart failure during or following cytokine release syndrome after CAR T-cell therapy. (2022) - Yoshihara, Kyoko; Orihara, Yoshiyuki; Hoshiyama, Tokiko; Tamaki, Hiroya; Sunayama, Isamu; Matsuda, Ikuo; Nishikawa, Akinori; Kumamoto, Tomoko; Samori, Mami; Utsunomiya, Nobuto; Min, Kyung-Duk; Asakura, Masanori; et al.
Abstract: Although cardiac dysfunction after chimeric antigen receptor (CAR) T-cell therapy has been increasingly reported, the underlying dynamics and pathogenesis are not well documented. Herein, we describe the clinical presentation and treatment for two patients who developed severe acute heart failure after CAR T-cell therapy. Both cases shared several common characteristics, including the bone marrow involvement at the time of CAR T-cell therapy and early onset of cytokine release syndrome (CRS) with fever developing on the day of CAR T-cell infusion. Patients with early onset and/or severe CRS should be carefully monitored for the possibility of heart failure.